2015
DOI: 10.1016/j.alcohol.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Emotional reactivity to incentive downshift as a correlated response to selection of high and low alcohol preferring mice and an influencing factor on ethanol intake

Abstract: Losing a job or significant other are examples of incentive loss that result in negative emotional reactions. The occurrence of negative life events is associated with increased drinking (Keyes et al., 2011). Further, certain genotypes are more likely drink alcohol in response to stressful negative life events (Blomeyer et al., 2008; Covault et al., 2007). Shared genetic factors may contribute to alcohol drinking and emotional reactivity, but this relationship is not currently well understood. We used an incen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…It is not clear whether the difference between HAP mice and B6 mice is specific to cSNC or whether this may indicate important differences between these populations in sensitivity to EtOH's rewarding effects. In other strain comparisons of cSNC, previous research has demonstrated that in a sucrose downshift paradigm, HAP replicates display greater cSNC than LAPs (Matson and Grahame, 2015). LAP mice will not drink EtOH, and therefore, we cannot assess whether EtOH cSNC would be found in them.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…It is not clear whether the difference between HAP mice and B6 mice is specific to cSNC or whether this may indicate important differences between these populations in sensitivity to EtOH's rewarding effects. In other strain comparisons of cSNC, previous research has demonstrated that in a sucrose downshift paradigm, HAP replicates display greater cSNC than LAPs (Matson and Grahame, 2015). LAP mice will not drink EtOH, and therefore, we cannot assess whether EtOH cSNC would be found in them.…”
Section: Discussionmentioning
confidence: 90%
“…The cognitive state induced by this downshift has classically been described as frustration (Amsel, 1962;Amsel, 1992). The relationship between EtOH and cSNC has primarily been studied within the context of assessing the ability of EtOH to relieve the frustrative effects associated with a sucrose downshift (Becker and Flaherty, 1982;Manzo et al, 2015;Manzo et al, 2014a;Matson and Grahame, 2015). Interestingly, cSNC is greater in mice genetically predisposed to excessive alcohol consumption than their corresponding low alcoholpreferring (LAP) lines when using a shift from 32% sucrose to 4% sucrose (Matson and Grahame, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This ‘protective’ effect of alcohol against frustration experienced during negative contrast fits the tension‐reduction hypothesis in that alcohol may reduce anxiety caused by reward downshift. As a negative experience, contrast can impact alcohol intake (Matson & Grahame, ) and vice versa (Cox, ). Our work provides a novel view of contrast over weekly experiences with an identical outcome paired with different alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work with rats has investigated alcohol's effect on different components of choice that include reward discrimination between quantitative (Martinetti et al ., ) and qualitative (Samson et al ., ) shifts in natural reward (i.e., sucrose) as well as preference for diverse outcomes including alcohol (Tomie et al ., ; Morales et al ., ). Separate work with mice has investigated alcohol's effect on relative valuation of sucrose outcomes using a standard incentive contrast paradigm (Matson & Grahame, ). These traditional approaches focus on a specific behavioral component which can be effective at assessing reward processing and choice.…”
Section: Introductionmentioning
confidence: 99%